Impact of smoking on frequency and spectrum of K-RAS and EGFR mutations in treatment naive Indonesian lung cancer patients - Masykura, Najmiatul (Lung Cancer (Auckl), 2019)
Background: Indonesia has the highest cigarette consumption in the world. We explored the clinical impact of smoking on the prevalence of EGFR and K-RAS mutations and survival in this prospective study. Methods: 143 treatment naive lung cancer patients were recruited from Persahabatan Hospital, a national tertiary hospital. DNA from cytological specimens had been extracted and genotyped for both EGFR and K-RAS mutations using a combination of PCR high resolution melting, restriction fragment length polymorphism (RFLP) and direct DNA sequencing. Results: EGFR mutation frequency in never smokers (NS) and ever smokers (ES) were 75% and 56% (p = 0.0401), respectively. In this cohort, the overall K-RAS mutation rate was 7%. Neither gender nor smoking history were associated with K-RAS mutation significantly. However, K-RAS transversion mutations were more common in male ES than transition mutations. Smoking history did not affect EGFR and K-RAS mutation frequencies in women. Concurrent EGFR/K-RAS mutation rate was 2.8% (4 of 143 patients). Four out of 91 EGFR mutation positive patients (4.4%) had simultaneous K-RAS mutation. Conclusions: In region where cigarette consumption is prevalent, smoking history affected frequencies of EGFR and K-RAS mutations, mainly in males.